Analisis Penentuan Harga Jual Berdasarkan Metode Cost PLus Pricing di Toko Lutfiyah Jaya dan di Toko Kak Ros Badung Bali - Lutfiyah (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2025)
The decision to determine the selling price and calculate the cost of goods sold is very important in increasing a small business because in addition to affecting the profit income that small businesses want to achieve, it can also affect survival. Determining the selling price to determine the price that will be set in the sales that will be marketed. Determining the selling price must be able to cover product costs, marketing costs and administrative costs that arise, and the desired profit. This study aims and focuses on finding out (1) The method of determining the selling price at Lutfiyah's shop and Kak Ros's shop in Badung Bali, (2) Analysis of determining the selling price at Lutfiyah Jaya and at Kak Ros's shop in Badung Bali based on the cost plus pricing method. This study uses a qualitative approach and this study uses producers as the object of research. Data collection techniques use observation, interviews, and documentation. Data analysis uses synergy starting from data collection, data reduction, and data presentation. The results of the study show (1) The method of determining the selling price at Lutfiyah Jaya and Kak Ros's shop in Badung Bali is only by adding 10% to the purchase price. (2) Analysis of determining the selling price at Lutfiyah Jaya and Kak Ros's shop in Badung Bali shows that the calculation of the company's production cost is lower than the calculation of the production cost using the full costing method by calculating the costs that have been and will be incurred by the company, then added with a profit mark-up. Meanwhile, by using the cost plus pricing method with a mark-up, the selling price becomes greater than according to the company.